Thrombotic events in COVID-19 patients: a case series and literature review - Zahra Javidarabshahi; Shohre Khatami; Roxana Rezazade; Neda Saeedian; Mahnaz Mozdourian (Babol University of Medical Sciences, 2020)
Background: Coronavirus disease 2019 (COVID-19) has rapidly emerged as a threatening pandemic. Clinical features of this pandemic involve a wide range of manifestations and are not completely known. Here, we present six cases of thrombotic events in patients with COVID-19. Case presentation: In this case series, we present six patients with confirmed COVID-19, according to real-time polymerase chain reaction, who were referred to our emergency department and were found to have thrombotic events. Pulmonary thromboembolism was diagnosed in three patients by computed tomography (CT) angiography. One patient was found to have deep vein thrombosis in Doppler ultrasonography. Another patient who presented with loss of consciousness, was finally diagnosed with cerebrovascular accident using brain CT. One of the patients had developed a myocardial infarction that was evident in the electrocardiography. Conclusion: It is ostensible that COVID-19 puts the patients at an increased risk for developing thrombotic conditions, possibly through formation of hyper-inflammatory and hyper-coagulative states. However, further prospective studies are recommended to confirm these findings.